Validity of caregivers’ reports on prior use of antibacterials in children under five years presenting to health facilities in Gulu, northern Uganda - Lanyero, Hindum; Ocan, Moses; Obua, Celestino; Stålsby Lundborg, Cecilia; Agaba, Katureebe; Kalyango, Joan N.; Eriksen, Jaran; Nanzigu, Sarah (PLoS ONE, 2021)
Given the frequent initiation of antibacterial treatment at home by caregivers of children under five years in low-income countries, there is a need to find out whether caregivers’ reports of prior antibacterial intake by their children before being brought to the healthcare facility are accurate. The aim of this study was to describe and validate caregivers’ reported use of antibacterials by their children prior to seeking care at the healthcare facility. Methods A cross sectional study was conducted among children under five years seeking care at healthcare facilities in Gulu district, northern Uganda. Using a researcher administered questionnaire, data were obtained from caregivers regarding reported prior antibacterial intake in their children. These reports were validated by comparing them to common antibacterial agents detected in blood and urine samples from the children using liquid chromatography with tandem mass spectrometry (LC-MS/MS) methods.
Keywords: Caregivers’ reports; Antibacterials; Children under five years; Health facilities; Gulu; Northern Uganda